2021
DOI: 10.1136/bmjopen-2020-046879
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal measurement approach to identify individuals with mild cognitive impairment: study protocol for a cross-sectional trial

Abstract: IntroductionThe diagnosis of mild cognitive impairment (MCI), that is, the transitory phase between normal age-related cognitive decline and dementia, remains a challenging task. It was observed that a multimodal approach (simultaneous analysis of several complementary modalities) can improve the classification accuracy. We will combine three noninvasive measurement modalities: functional near-infrared spectroscopy (fNIRS), electroencephalography and heart rate variability via ECG. Our aim is to explore neurop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 127 publications
0
10
0
Order By: Relevance
“…In the current study, older adults with aMCI, naMCI, and healthy controls (HC) were recruited as part of a larger project (MyFit study [ 40 ]) through advertisements in local newspapers, flyers, posters, word of mouth, and by using existing databases. After recruitment, the individuals were screened for eligibility based on the following inclusion criteria: (i) 50 to 80 years old, (ii) native German-speaking, and (iii) able to manage everyday activities independently.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current study, older adults with aMCI, naMCI, and healthy controls (HC) were recruited as part of a larger project (MyFit study [ 40 ]) through advertisements in local newspapers, flyers, posters, word of mouth, and by using existing databases. After recruitment, the individuals were screened for eligibility based on the following inclusion criteria: (i) 50 to 80 years old, (ii) native German-speaking, and (iii) able to manage everyday activities independently.…”
Section: Methodsmentioning
confidence: 99%
“…In accordance with the recommendations in the literature, participants with a performance below −1.5 SD in the age, sex, and education-adjusted z-value in at least one of these two cognitive subtests of the CERAD test battery were classified as aMCI [ 48 ]. Please note that this study is part of a larger project (MyFit study [ 40 ]) and in the current study we performed the analysis of selected and secondary outcome measures of this larger trial. Thus, no additional sample size calculation was performed as the available data of participants who had been recruited for the MyFit study were used (see reference [ 40 ] for more detailed information and sample size calculation of the MyFit study).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cognitive tasks lasted for about 30 min. A more detailed description of the study procedures can be found elsewhere [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…Prior to the experiment, participants were allowed to practice both tasks to adequately familiarize them with the procedures. A detailed description of the procedure of the cognitive tasks can be found elsewhere [ 44 ].…”
Section: Methodsmentioning
confidence: 99%